La gamificación para la enseñanza-aprendizaje de Lengua y Literatura en sexto grado, Escuela Matilde Hidalgo de Procel, Loja 2024- 2025 - Romero Guevara, Anshely Mayte (2025)
The present research work called Gamification for the teaching-learning of Language and Literature, had as general objective: To diagnose the incidence of gamification by developing a didactic proposal for the improvement of the teaching-learning process of Language and Literature of sixth grade students of the Matilde Hidalgo de Procel School; the same that was integrated by three specific objectives: the first, To diagnose the main learning difficulties that students present in the subject of Language and Literature; the second, To identify the teachinglearning strategies that the teacher uses to impart knowledge in the subject of Language and Literature; and, the third, To develop a didactic proposal based on gamification to improve the teaching-learning process of Language and Literature. A descriptive type research was used with a mixed approach and non experimental design, for the development of the research the analytical, synthetic, deductive, inductive, hermeneutic, and statistical methods were taken into account; Among the techniques are diagnostic evaluation and interviews, and the instruments used were: an interview guide and a structured questionnaire for data collection. The population was made up of students from the elementary level, from which twenty students and a sixth grade teacher were chosen through a non-probabilistic sampling of intention or convenience. The results show that 75% of the students are close to achieving the required learning; and 20% do not achieve the required learning, showing problems such as: writing, spelling rules, text comprehension. Therefore, the use of innovative strategies, such as gamification, is important since it influences the teaching-learning process of Language and Literature, facilitating the acquisition of skills and improving academic performance